Predictors of Health-Promoting Lifestyle in Pregnant Women Based on Pender’s Health Promotion Model - Jalili Bahabadi F; Estebsari F; Rohani C; Rahimi Khalifeh Kandi Z; Sefidkar R; Mostafaei D (Dove Medical Press, 2020)
Farideh Jalili Bahabadi, 1 Fatemeh Estebsari, 2 Camelia Rohani, 3 Zahra Rahimi Khalifeh Kandi, 4 Reyhaneh Sefidkar, 5 Davoud Mostafaei 6 1Student Research Committee, Community Health Nursing Department, School of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 2Community Health Nursing Department, School of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 3Community Health Nursing Department, School of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 4Department of Public Health, Iran University of Medical Sciences, Tehran, Iran; 5Department of Biostatistics, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 6Health Services Management, Shahid Beheshti University of Medical Sciences, Tehran, IranCorrespondence: Fatemeh EstebsariDepartment of Community Health Nursing, School of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, IranTel +98-2188655367 (330)Fax +98-2188202518Email fa_estebsari@yahoo.comBackground and Objectives: Pregnancy causes changes in women’s lifestyle; therefore, their health-promoting behaviors should be improved in order to avoid problems during this critical period, which requires knowledge of the factors affecting these behaviors. This study was conducted to determine the predictors of health-promoting lifestyles in pregnant women based on Pender’s health promotion model constructs.Methods: This descriptive study was carried out on 300 pregnant women in their second and third trimesters of pregnancy and sought to determine the correlation between lifestyle and the constructs of Pender’s health promotion model. Data were collected using a demographic questionnaire, the Health Promoting Lifestyle Profile II (HPLP-II) and a questionnaire based on Pender’s model constructs. Data were analyzed using descriptive and analytical statistics.Findings: A health-promoting lifestyle had a significant positive correlation with the constructs of social support and perceived benefits and a significant negative correlation with the construct of perceived barriers (P< 0.05). A health-promoting lifestyle also had a significant relationship with the constructs of perceived barriers, social support and perceived benefits in pregnant women (P< 0.05) based on the results of the regression analysis. The regression coefficients showed that all the three variables can significantly explain the variance in health promoting lifestyles in pregnant women (P< 0.05).Conclusion: According to the results of the present study and based on the constructs of Pender’s health promotion model, social support, perceived benefits and perceived barriers were the most important predictors of health-promoting lifestyles in pregnant women. These predictor constructs are recommended to be further considered in designing and implementing training packages and interventions for promoting pregnant women’s lifestyle.Keywords: pregnant women, lifestyle, health promotion model, health-promoting behaviors